Selected traumatic factors and their impact on ill newborns in hospital conditions including the Neonatal Intensive Care Unit. Part I. Noise and artificial lighting - Kruszecka-Krówka, Agnieszka; Cepuch, Grażyna (Nursing Problems / Problemy Pielęgniarstwa, 2018)
Hospitalised newborns, especially those born prematurely, are exposed to a number of traumatic stimuli, such as noise, artificial lighting, and overly intense and frequent touching. The above stressors, separation from the mother, as well as care and diagnostic-therapeutic activities, including specialist invasive procedures, can cause or exacerbate severe pain. Given the specificity of the neonatal period, the exposure to traumatic factors generates the risk of distant, negative consequences. The influence of traumatic factors on newborns disturbs the process of adaptation and has a negative impact on the development of the central nervous system, psychological development and the formation of the organs of sensory perception. In their work, nurses should seek to optimize care by limiting the destructive impact of environmental factors on the neonatal patient and reduce the risk of early and distant complications in the biopsychosocial area.